Elomar Figueira Mello’s music: context and style beyond popular and classical (Per Musi, 2014)
Discussion about the compositional processes in the work of Elomar Figueira Mello, here considered in two ways: regionalist and popular (as found in his cancioneiro) and classical (represented mainly by his operas). His work integrates several styles such as the “cantoria nordestina” (Brazilian northeastern way of singing), the flamenco style, the “seresta”, the “tango”, Christian anthems e and the classical music. This integration produces harmonic contexts with blends of modalism and tonalism and complex phrase forms derived mainly from the regional dialects from the south of Bahia. The style of Elomar reveals some of the “lost links” in the Brazilian music formation through the admirable hybridism of several styles and technics.